Low-Molecular-Weight Heparins in the Cardiac Catheterization Laboratory - Kadakia, Rajan A. (2004)
We describe the unique properties of low-molecular-weight heparins and review studies of the use of these agents in the catheterization laboratory for percutaneous coronary intervention. Recent data regarding bedside monitoring of low-molecular-weight heparin activity are also discussed, as are ongoing and future studies that should be of assistance to clinicians as they consider expanding the use of this newer form of antithrombotic therapy.